Efektifitas Epinefrin Tambahan Anestesi Lokal dan Mengevaluasi Mitos dan Realita “Never Inject Local Anesthesia with Epinephrine into Akral, Ears and Penis - Sitorus, Gunawan Leonard (Riviera Publishing, 2025)
The use of Epinephrine as a mixture in local anesthesia has been widely used in various types of concentrations. The dogma and myth of the combination of local anesthesia with epinephrine is conventionally contraindicated in the acradial and penile areas due to concerns of potential necrosis due to impaired blood flow. The addition of epinephrine to local anesthesia has been shown to replace tourniquets. An in-depth analysis of the medical literature since 1903 has been conducted, including case reports, reviews, and clinical trials involving the effectiveness of administering epinephrine under local anesthesia as well as its combined risk of necrosis in the acral and penile areas. A thorough search was conducted on Pubmed and google scholar using Keywords: epinephrine, local anesthesia, necrosis fingers, ears, eyelids, and penis. No evidence was found in the literature regarding a link between epinephrine as a vasoconstrictor and achoral or penile necrosis. Procaine is believed to be the cause of tissue necrosis under local anesthesia before 1950. The use of epinephrine in addition to local anesthesia has been shown to increase the effectiveness of analgesia as well as Procaine is believed to be responsible for tissue necrosis.